The Routledge Handbook of Chinese Studies (Taylor & Francis, 2021)
Chinese, language learning, foreign policy, Chinese political system, domestic governance, international relations, Chinese culture, Chinese literature, Chinese history, Chinese sociology, Chinese opposition, Chinese activism, Chinese people, Chinese society, Chinese studies
English
Keywords: Language: reference & general; Language; Chinese, language learning, foreign policy, Chinese political system, domestic governance, international relations, Chinese culture, Chinese literature, Chinese history, Chinese sociology, Chinese opposition, Chinese activism, Chinese people, Chinese society, Chinese studies